1965
DOI: 10.1021/jf60138a001
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide Metabolism, Nature of Toxic Metabolites Formed in Mammals, Insects, and Plants from 3-(Dimethoxyphosphinyloxy)-N-N-dimethyl-cis-croton-amide and Its N-Methyl Analog

Abstract: Bidrin, 3-(dimethoxyphosphinyloxy)-N,N-dimethyl-c/s-crotonamide, is metabolized to yield trace amounts of 3-(dimethoxyphosphinyloxy)-N-methyl-N-hydroxymethyl-c/s-crotonamide and larger amounts of 3-(dimethoxyphosphinyloxy)-N-methyl-c/s-crotonamide (SD 9129). SD 9129 is further metabolized to yield 3-(dimethoxyphosphinyloxy)-N-hydroxymethyl-c/s-crotonamide and 3-(dimethoxyphosphinyloxy)-c/s-crotonamide. The toxicity to both insects and mammals increased upon successive N-demethylation. Balance studies on the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0

Year Published

1966
1966
2006
2006

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(50 citation statements)
references
References 12 publications
5
45
0
Order By: Relevance
“…Phosphatase activities were observed in both cultures, and it was suggested that the phosphates identified may be mono‐ and dimethyl phosphates (Bhadbhade et al , 2002b). Dimethyl‐ and monomethyl phosphates were involved as intermediates in monocrotophos degradation in plants and animals (Menzer & Cassida, 1965; Muck, 1994). Another intermediate identified during monocrotophos degradation was methylamine, produced by an esterase enzyme.…”
Section: Microbial Degradation Of Organophosphorus Compoundsmentioning
confidence: 99%
“…Phosphatase activities were observed in both cultures, and it was suggested that the phosphates identified may be mono‐ and dimethyl phosphates (Bhadbhade et al , 2002b). Dimethyl‐ and monomethyl phosphates were involved as intermediates in monocrotophos degradation in plants and animals (Menzer & Cassida, 1965; Muck, 1994). Another intermediate identified during monocrotophos degradation was methylamine, produced by an esterase enzyme.…”
Section: Microbial Degradation Of Organophosphorus Compoundsmentioning
confidence: 99%
“…zThe metabolic fate of MCP in plants and animals is well documented by Bull and Lindquist (1964), Menzer and Cassida (1965), Beynon et al (1973) and Mucke (1994). Bacteria capable of degrading several pesticides have been isolated from soil.…”
Section: Introductionmentioning
confidence: 99%
“…The consecutive steps of N-methyl hydroxylation and de methylation of the N,N-dimethyl group of dicrotophos were initially indicated by in vivo studies (Bull and Lindquist, 1964). The sequence was later elucidated with an in vitro microsomal system using an elegant double-labeling C 2 p and 14C) technique (Menzer and Casida, 1965). Subsequent studies have shown an identical type of N-ethyl oxidation for a closely related insecticide, phosphamidon (Bull etat., 1967;Clemons and Menzer, 1968;Lucier and Menzer, 1971).…”
Section: 1 0- $- and N-alkyl Hydroxylationmentioning
confidence: 99%